1979
DOI: 10.1079/bjn19790009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary proteinase inhibitors from field bean (Vicia faba L.) and field-bean meal on pancreatic function in the rat

Abstract: I . Male weanling rats were fed casein diets containing 1.25, 2.5, 5.0 and 10 g/kg active or autoclaved proteinase inhibitors (PI) from field bean (Viciu faba L.), and raw-and autoclaved-field-bean meal (FBM) diets. After 7, 14 and 2 1 d on the diets pancreas weights were measured and pancreas and intestinal trypsin (EC 3.4.4.4) and chymotrypsin (EC 3.4.4.5) assayed.2. Pancreas weights increased on the raw FBM and active-PI-supplemented diets. Maximum pancreatic hypertrophy measured as the percentage increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

1983
1983
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 18 publications
0
8
1
1
Order By: Relevance
“…In particular, standard deviations of the protease activities in the pancreases of rats fed a RBPC diet were larger than those of the other groups. The pancreatic hypertrophy as well as the growth depression have been observed by other investigators (14)(15)(16)(17). Although our present data are ambiguous for the judgement of pancreatic enlargement, the possibility that slight pancreatic hypertrophy was caused by the …”
Section: And Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In particular, standard deviations of the protease activities in the pancreases of rats fed a RBPC diet were larger than those of the other groups. The pancreatic hypertrophy as well as the growth depression have been observed by other investigators (14)(15)(16)(17). Although our present data are ambiguous for the judgement of pancreatic enlargement, the possibility that slight pancreatic hypertrophy was caused by the …”
Section: And Discussioncontrasting
confidence: 41%
“…However, it seems that there is such a possibility. Many workers (14)(15)(16) have reported that the growth depression is observed in animals fed a diet containing a trypsin inhibitor, even though the apparent nitrogen digestibilities are the same between the diets with a trypsin inhibitor and without the inhibitor.…”
Section: And Discussionmentioning
confidence: 99%
“…When protease inhibitors are isolated and included in the diets of rats, physiological responses such as pancreatic hypertrophy, decreased amounts of trypsin and chymotrypsin in the pancreas, increased amounts of these enzymes in the intestine and growth depression are observed. The significantly increased pancreas relative weight seen in experiment 1 among birds fed on a diet containing 500 g/kg of RFB, is associated with the presence of antiprotease factor(s) (Abbey et al, 1979). This is corroborated by the histological examination conducted on the pancreas with alteration of acinar cells (Figs.…”
Section: Cytopathologymentioning
confidence: 74%
“…Pancreatic hypertrophy in birds fed on diets containing TI (Levison et al 1979), lectin (Abbey et al 1979;Grant et al 1987) or tannin (Ahmed et al 1991) has been tacitly ascribed in its entirety to the direct effect of the antinutritional substance. However, the results of the present experiment show that merely limiting the feed intake of birds fed on a tannin-free diet can result in a higher relative pancreas weight compared with those which are fed ad lib.…”
Section: Discussionmentioning
confidence: 99%